Community‐Level Responses to Iron Availability in Open Ocean Plankton Ecosystems. Issue 3 (20th March 2019) - Caputi, Luigi; Carradec, Quentin; Eveillard, Damien; Kirilovsky, Amos; Pelletier, Eric; Pierella Karlusich, Juan J.; Rocha Jimenez Vieira, Fabio; Villar, Emilie; Chaffron, Samuel; Malviya, Shruti; Scalco, Eleonora; Acinas, Silvia G.; et al.
Abstract: Predicting responses of plankton to variations in essential nutrients is hampered by limited in situ measurements, a poor understanding of community composition, and the lack of reference gene catalogs for key taxa. Iron is a key driver of plankton dynamics and, therefore, of global biogeochemical cycles and climate. To assess the impact of iron availability on plankton communities, we explored the comprehensive bio‐oceanographic and bio‐omics data sets from Tara Oceans in the context of the iron products from two state‐of‐the‐art global scale biogeochemical models. We obtained novel information about adaptation and acclimation toward iron in a range of phytoplankton, including picocyanobacteria and diatoms, and identified whole subcommunities covarying with iron. Many of the observed global patterns were recapitulated in the Marquesas archipelago, where frequent plankton blooms are believed to be caused by natural iron fertilization, although they are not captured in large‐scale biogeochemical models. This work provides a proof of concept that integrative analyses, spanning from genes to ecosystems and viruses to zooplankton, can disentangle the complexity of plankton communities and can lead to more accurate formulations of resource bioavailability in biogeochemical models, thus improving our understanding of plankton resilience in a changing environment. Plain Language Summary: Marine phytoplankton require iron for their growth and proliferation. According to John Martin's iron hypothesis, fertilizing the ocean with iron could dramatically increase photosynthetic activity, thus representing a biological means to counteract global warming. However, while there is a constantly growing knowledge of how iron is distributed in the ocean and about its role in cellular processes in marine photosynthetic groups such as diatoms and cyanobacteria, less is known about how iron availability shapes plankton communities and how they respond to it. In the present work, we exploited recently published Tara Oceans data sets to address these questions. We first defined specific subcommunities of co‐occurring organisms that co‐vary with iron availability in the oceans. We then identified specific patterns of adaptation and acclimation to iron in different groups of phytoplankton. Finally, we validated our global results at local scale, specifically in the Marquesas archipelago, where recurrent phytoplankton blooms are believed to be a result of iron fertilization. By integrating global data with a localized response, we provide a framework for understanding the resilience of plankton ecosystems in a changing environment. Key Points: Coherent assemblages of taxa covarying with iron at global level are identified in plankton communities Functional responses to iron availability involve both changes in copy numbers of iron‐responsive genes and their transcriptional regulation Plankton responses to local variations in iron concentrations recapitulate global patterns